Motivational Strategies, Language Learning Strategies, and Literal and Inferential Comprehension in Second Language Chinese Reading: A Structural Equation Modeling Study - Lin, Lin; Lam, Wai-Ip; Tse, Shek Kam (Frontiers in Psychology, 2021)
Motivational strategies have been recognized as a crucial but insufficiently explored component in second language (L2) learning. This study intends to explore the relationships between motivational strategies, language learning strategies, and literal and inferential comprehension in L2 Chinese reading. Data were collected from 547 international students of universities in mainland China through a strategy use questionnaire and a Chinese reading test. The analysis of the structural equation model indicated that motivational strategies indirectly affected literal comprehension through the mediation of learning strategies. Moreover, motivational strategies were found to directly affect inferential comprehension. The results emphasize the need for a more sophisticated analysis of the motivational strategies and language learning strategies in L2 Chinese reading.